2020
DOI: 10.1002/hep4.1599
|View full text |Cite
|
Sign up to set email alerts
|

The Growing Burden of Disability Related to Nonalcoholic Fatty Liver Disease: Data From the Global Burden of Disease 2007‐2017

Abstract: Chronic liver disease (CLD) is a growing cause of morbidity and mortality worldwide. The burden of CLD varies according to etiology and geographic location. We assessed the global burden of disability from the most important complications of CLD (cirrhosis and liver cancer [LC]) according to the most common etiologies between 2007 and 2017. We obtained years living with disability (YLD), years of life lost (YLL), and disability‐adjusted life‐years (DALYs) data from the Global Burden of Disease 2017 study. Betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 40 publications
2
56
0
1
Order By: Relevance
“…This study reported that the number of prevalent cases for compensated cirrhosis due to NASH doubled over the study period, while the number for decompensated cirrhosis due to NASH tripled ( 47 ). Another study assessing the burden of NAFLD-/NASH-related burden using the same Global Burden of Disease database revealed that between 2007 and 2017, cirrhosis DALY due to NAFLD/NASH increased by 23.4%, while liver cancer DALY due to NAFLD/NASH increased by 37.5% ( 48 ).…”
Section: Clinical and Economical Burden Of Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…This study reported that the number of prevalent cases for compensated cirrhosis due to NASH doubled over the study period, while the number for decompensated cirrhosis due to NASH tripled ( 47 ). Another study assessing the burden of NAFLD-/NASH-related burden using the same Global Burden of Disease database revealed that between 2007 and 2017, cirrhosis DALY due to NAFLD/NASH increased by 23.4%, while liver cancer DALY due to NAFLD/NASH increased by 37.5% ( 48 ).…”
Section: Clinical and Economical Burden Of Nafldmentioning
confidence: 99%
“…Global Burden of Disease database revealed that between 2007 and 2017, cirrhosis DALY due to NAFLD/NASH increased by 23.4%, while liver cancer DALY due to NAFLD/NASH increased by 37.5%(49). , and indirect costs, respectively.…”
mentioning
confidence: 99%
“…Approximately 25-40% of the general western world population develop NAFLD throughout their lives, of which approximately 30% progress to NASH(5-7), which is the leading cause for a liver transplant(8, 9) with overall estimated economic burden of $103 billion annually and projected 10-year burden of >$1 trillion in US alone (5, 7,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…While NAFLD is considered a mild condition, Non-Alcoholic Steatohepatitis (NASH), the severe form of the disease, is de ned by in ammation and cell damage in addition to the fat accumulation. NASH increases the risk of developing liver brosis and may lead to cirrhosis and end-stage liver disease (2-4).Approximately 25-40% of the general western world population develop NAFLD throughout their lives, of which approximately 30% progress to NASH(5-7), which is the leading cause for a liver transplant(8, 9) with overall estimated economic burden of $103 billion annually and projected 10-year burden of >$1 trillion in US alone (5, 7,10,11).Despite truly epidemic proportions, diagnostic options for NASH are very limited (12, 13). Most NAFLD and NASH patients are asymptomatic until relatively late stages of the disease and suspicion of NASH often stems from coincidental ndings(2).…”
mentioning
confidence: 99%
“…5 As a result of high frequency of metabolic comorbidities in patients with NAFLD and also the growing burden of disability related to chronic liver diseases, global policies are required to address the disability burden of NAFLD worldwide. 6 Pathogenesis of NAFLD is complicated and multifactorial. 7According to the "two-hit" theory proposed by Day and Jams, insulin resistance (IR) leads to hepatic accumulation of triglyceride, and then steatosis, making the liver more vulnerable to a "second hit" resulting in oxidative stress, endoplasmic reticulum stress and mitochondrial dysfunction, and ultimately leading to inflammation, fibrosis and cancer.…”
mentioning
confidence: 99%